Usability Evaluation of Iraqi News Applications - Alashaab, Husni Refat Husni; Salim, Sofia Mohammed (مجلة الشرق الأوسط للعلوم الإنسانية والثقافية, 2024)
The research examines and evaluates the usability of Iraqi news applications, (Alrabiaa) and (Alsumaria), using regular observation and the heuristics evaluation method based on a set of criteria that were derived from the basic rules of ease of use. The research is descriptive research, the survey methodology steps were followed to achieve the objectives. The researchers reached a number of conclusions, including that the applications considered the general rules and principles of usability, despite the existence of errors in terms of format and content, which can be addressed to obtain a better user experience, such as font colors, text alignment, options to change the type of view and user interface, and the appearance of ads in published news. The researchers also noted a significant correlation between the applications and their parent media institutions, in addition to the superiority of (Alsumaria) application over (Alrabiaa) application, in terms of its media services that were characterized by speed, efficiency and ease of access.